EFEKTIVITAS PENGGUNAAN MEDIA AUDIO VISUAL TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN AL QUR’AN HADIST DI KELAS IX MTS SALAFIYAH SYAFIIYAH BANDUNG DIWEK JOMBANG - Nur Hamidatul Arifah; Hidayatur Rohmah (Universitas KH. A. Wahab Hasbullah, 2020)
This study aims to determine students' motivation towards the use of audio-visual media in the Al-Qur'an Hadith subjects at MTs Salafiyah Syafiiyah Bandung. To achieve these objectives the researchers used data collection techniques through interviews, questionnaires, and documentation. The data is processed using quantitative analysis to determine the effect of learning media on student motivation. This research includes the type of field research or the field of research that is the author conducts research directly to the location to obtain and collect data. The results showed that the level of use of instructional media was classified in either category. The level of student learning motivation is classified as